Networked and embedded scientific experiments will improve restoration outcomes. Issue 5 (7th May 2018) - Gellie, Nicholas JC; Breed, Martin F; Mortimer, Peter E; Harrison, Rhett D; Xu, Jianchu; Lowe, Andrew J
Abstract : Vast areas of degraded land have proliferated worldwide. In response to this transformation, ambitious targets have been set to restore degraded ecosystems, such as the the Bonn Challenge, which aims to restore 350 million ha of forestland by 2030. Achieving such goals will require a larger evidence base of restoration studies, which could be realized by systematically embedding scientific experiments within restoration programs. We examine the feasibility of this strategy with examples of successful transdisciplinary research involving embedded experiments in associated fields, and recommend that such field sites be linked to create a global network of embedded experiments. To unify a networked approach, we call on restoration stakeholders to develop acceptable industry standards of experimental design. Finally, we suggest how to use this strategy effectively to meet the biome‐scale challenges of the coming decades.